Relationship Between the Fixed Point Theorem and the EM Algorithm - Lanani, Ahsene (Journal of Informatics and Mathematical Sciences, 2018)
When we are confronted with solving nonlinear equations which do not admit explicit solutions, we must use approximate methods based on iterative processes or algorithms. One of the best known iterative methods is the fixed point theorem, often applied in analysis or algebra. In our case, we will apply this method in a stochastic context. By means of this application, we show the relationship between this method and the EM algorithm, which is an iterative process, often applied in statistics.